Optimal location and sizing of distributed generation for economic operation in power system using evolutionary programming optimization technique / Mohd Hafiz Abu Chek - Abu Chek, Mohd Hafiz (2007)
This project report presents a new technique to find the optimum location and size of distributed generation (DG) in a power system using an Evolutionary Programming optimization technique. This study will utilize concept of Evolutionary Programming (EP) by using MATLAB software. The study indicates several fitness function include total loss minimization, total cost minimization and maximisation of voltage level in power system. Comparison was made in order to determine the best fitness function to be used for solving this technique. The proposed technique is tested on IEEE 26 bus reliability test system.